2006
DOI: 10.1128/iai.74.5.2887-2893.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Antibodies to Merozoite Surface Antigens Are Associated with Recovery from Chloroquine-ResistantPlasmodium falciparumin Gambian Children

Abstract: We examined the hypothesis that recovery from uncomplicated malaria in patients carrying drug-resistant Plasmodium falciparum is a measure of acquired functional immunity and may therefore be associated with humoral responses to candidate vaccine antigens. Gambian children with malaria were treated with chloroquine in 28-day trials, and recovery was defined primarily as the absence of severe clinical malaria at any time and absence of parasitemia with fever after 3 days. Plasma samples from these children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…This finding is in contrast to previous studies that found anti-MSP-1 19 levels at the time of treatment to be protective against treatment failure [32], [33]. While our finding may represent a spurious result, given the marginal significance when taking into account multiple testing, there are some biologically plausible mechanisms for this seemingly paradoxical association.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to previous studies that found anti-MSP-1 19 levels at the time of treatment to be protective against treatment failure [32], [33]. While our finding may represent a spurious result, given the marginal significance when taking into account multiple testing, there are some biologically plausible mechanisms for this seemingly paradoxical association.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies have found associations between positive or high IgG responses to a number of antigens (NANP repeat of CSP [39], K1 and MAD20 block 2 variants of MSP-1 [34], MSP-1 19 [32], [33], and GLURP-R0 and R2 [36]) and protection from treatment failure. Three of these studies included assessment of AMA-1 antibodies in their analyses, but these did not show strong associations between anti-AMA-1 levels and clearance of parasitemia [33], [36], [37]. Differences between our results and prior studies may be attributable to the antimalarial therapy used, due to varying efficacy and pharmacokinetics; differences in the epidemiological setting and patient characteristics; different means of assessing treatment outcome; and the use of different laboratory and analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Low-level exposure related to subtherapeutic drug concentrations of antimalarials due to moderate resistance also has been shown to have important effects on immune responses (25). Higher titers of IgG responses to MSP-1 19 enhanced the likelihood of parasitological clearance in individuals treated with a suboptimal drug regimen, and it was suggested that recovery from uncomplicated malaria in patients carrying drug-resistant P. falciparum is a phenotypic marker of acquired functional immunity (12,13,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, this relationship is not seen to hold, as people in higher transmission areas have more acquired immunity, and this appears to be a more important determinant of treatment success for a population than the prevalence of drug resistance alleles (80). Within local populations, individual treatment success with chloroquine is strongly age dependent in a manner that appears to clearly reflect acquired immunity (55) and correlates with acquired antibodies to merozoite antigens (148). There are effective antimalarial drugs that have not yet been widely used in populations in areas of endemicity, generally because they are too expensive.…”
Section: Surveillance and Preventionmentioning
confidence: 99%